KNO3 supported on three-dimensionally ordered macroporous La0.8Ce0.2Mn1−xFexO3 for soot removal. Issue 8 (5th February 2016) - Feng, Nengjie; Meng, Jie; Wu, Yang; Chen, Chong; Wang, Lei; Gao, Lu; Wan, Hui; Guan, Guofeng
Abstract : The KNO3 supported on 3DOM La0.8 Ce0.2 Mn1− x Fe x O3 perovskites have been prepared and used for soot removal. The presence of potassium nitrate can accelerate the soot combustion at both low and high temperature. The catalysts exhibit high activities for soot combustion. Abstract : Three-dimensionally ordered macroporous (3DOM) La0.8 Ce0.2 Mn1− x Fe x O3 perovskites were successfully prepared by a colloidal crystal template method and KNO3 -supported 3DOM La0.8 Ce0.2 Mn1− x Fe x O3 catalysts were prepared by a wetness impregnation method. Physicochemical properties of these catalysts were characterized by XRD, FT-IR, FESEM, TEM, BET, H2 -TPR, O2 -TPD, and XPS techniques and their catalytic performances were evaluated by soot combustion. All these perovskites possessed a well-ordered 3DOM structure, and KNO3 was highly dispersed on the skeleton of the supporters without changing the morphology and crystal structure of the perovskites. The 3DOM structure provides an increased contact area between the catalyst and soot. Besides, partial replacement of Mn by Fe into the perovskites increased the surface area and reducibility. The introduction of K ions increased the amount of active oxygen species in the catalysts, which could accelerate soot combustion at low temperature. On the other hand, the NO3 − species brought by KNO3 were beneficial to the reaction at high temperature. Among all the samples, the 3DOM K/La0.8 Ce0.2 Mn0.6 Fe0.4 O3 exhibited the highest catalytic performance with the lowest T 50 at 379 °C.